Care of People with Epilepsy in Rural Medical Centre of Developing Countries with Limited Resources: During the COVID-19 Pandemic - Verma, A.; Kumar, A. (Kathmandu University Medical Journal, 2020)
Coronavirus disease 2019 (COVID‐19) has become a pandemic disease globally. This extraordinary situation is posing an enormous burden on the healthcare systems worldwide and is reshaping the way in which chronic disorders are managed. Pandemic has made epilepsy care even more demanding in rural part of developing countries. We outline the adverse circumstances in epilepsy care induced by the pandemic; propose emergency management and follow up care of people with epilepsy. There is a requirement for public health systems in resource poor countries to improve awareness, implement proper strategies of triage, acute treatment, telemedicine services and virtual check-ins.